Pemberdayaan Kesehatan Lansia melalui Pemeriksaan Tekanan Darah, dan Senam Lansia di Kelurahan Partali Toruan Hutabarat - Siska Simanungkalit; Yohana Purba; Djuahadi Silitonga; Rotua Samosir (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The aim of this research is to assess the effectiveness of the elderly health program run by the Partali Toruan Hutabarat Village, with special emphasis on participatory sessions specifically for the elderly and periodic blood pressure. The analytical method used is an intervention study with data collection both before and after the intervention. The results show a significant increase in understanding of the importance of regularly cleaning and using natural materials for the health of local communities. Apart from that, there was also a negative impact seen on the average blood pressure levels in the group of program participants. All of this highlights the important role of community initiatives in improving the health of the elderly through integrated and sustainable efforts, such as health education and promotion of active lifestyles.